Preliminary observations on the eating behavior in a selected group of Jordanian adults with CVD and type 2 diabetes - Alkhatib, Buthaina; Agraib, Lana M.; Al-Shami, Islam (Acta Biomedica Atenei Parmensis, 2025)
Background: Various factors have influenced eating behaviors, including the occurrence of diseases. Aims: To evaluate eating behaviors and how disease incidence affects them in Jordan’s healthy population. Methods: A cross-sectional study was conducted on 1054 males and 1361 females (>18 years) between March and May 2022. Participants were categorized into two groups: those with diseases (diabetes, cardiovascular diseases (CVD), and comorbidities) and those with no diseases. Eating behaviors, including meal timing and frequency, late-night eating, and fast-food consumption, were evaluated. Results: Regardless of age group, most participants tended not to skip meals, consumed two to three meals daily, had one to three snacks, ate lunch between 1:00 and 6:00 p.m., and did not consume food late in the day. The most consumed food group is cereals (males: 65.5% for healthy and 60.2% for diseased; females: 64.2% for healthy and 61.0% for diseased). The prevalence of the most frequent food consumption (1-5 times per week) was higher in healthy participants (67.4%) compared to diseased participants (49.6%) (p < 0.001). Diseased participants reported significantly higher consumption of vegetables in the group (10.3%) compared to healthy participants (5.0%, p<0.001). The most frequently missed or under-consumed food group was dairy products (48.0% for healthy individuals and 41.0% for those with disease). The prevalence of morning and night eating was 42.8% and 26.6% among the diseased participants, compared to healthy participants (35.6% and 32.9%, respectively). Conclusion: Even if Jordanians’ eating behaviors contradict healthy eating behaviors, the presence of diseases is a beneficial factor that can enhance healthy eating behaviors. (www.actabiomedica.it)